If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = u + 6 Reorder the terms: 4 = 6 + u Solving 4 = 6 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 4 + -1u = 6 + u + -1u Combine like terms: u + -1u = 0 4 + -1u = 6 + 0 4 + -1u = 6 Add '-4' to each side of the equation. 4 + -4 + -1u = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -1u = 6 + -4 -1u = 6 + -4 Combine like terms: 6 + -4 = 2 -1u = 2 Divide each side by '-1'. u = -2 Simplifying u = -2
| 40a^2+195+140=0 | | 8xy^3/6y^5 | | 4X-3=2-6X | | x^2-21x-216=0 | | (n+6)((n+6)-10)=200 | | -(7x-3)-(4x-5)+11=-3(x-1)-(11X+2)+3 | | 8x^204=28 | | (n^(-4/15))*(5n^(3/5)) | | 3/75=x/10 | | 6y+(3y+3)=16 | | n^-4/15*5n^3/5 | | -5m^2+245=0 | | ln(3x+1)+ln(x)=ln(2) | | 3(2y+3)=-3y-9 | | Y=-16x^2+384 | | 3n+5forn=4 | | 5x-1.2=9x-.8 | | 4+4-6x=35 | | 3(2x-1)=5x+2 | | 7/14= | | (-5/6)y(-3/4) | | -18=(9-x)/2 | | (-5/6)y | | -18=9-x/2 | | 75g^3=143g | | 4x+.4=2x | | x^2+10x+27=8 | | (9xy)^1/5 | | -m^2-4m+21=0 | | 2m+m+3m= | | -3y+9x=-3 | | x^2-3x+4=8 |